2013
DOI: 10.1002/pssc.201200878
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of CuInS2 thin films from materials grown by mechanochemical method

Abstract: Optical second harmonic generation (SHG) has been studied in TlMeX2 (Me=In,Ga, X=S,Se,Te) compounds with layered and chain crystalline structures. For layered TlInS2 and TlGaSe2, SHG signal has been observed in a range of temperatures below the point of phase transition into ferroelectric phase for which asymmetry is prominent. On the other hand, the chain TlInSe2 and TlGaTe2 have shown SHG signal at a temperature above 270 and 293K, respectively. Both the TlInSe2 and TlGaTe2 have symmetry centre at room tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The diffraction peaks corresponding to the CuS phase along with the CuInS 2 phase also appeared in the films annealed below 300 °C. 16) It has been shown that the CuS layer does not homogeneously cover the surface of the films. 13,23) Most probably, these particles are CuS crystals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diffraction peaks corresponding to the CuS phase along with the CuInS 2 phase also appeared in the films annealed below 300 °C. 16) It has been shown that the CuS layer does not homogeneously cover the surface of the films. 13,23) Most probably, these particles are CuS crystals.…”
Section: Resultsmentioning
confidence: 99%
“…However, the source materials were grown using crystal growth from the melt, and the thin films prepared had low crystallinity. In our previous paper, CuInS 2 thin films were prepared using single-source thermal evaporation with a ternary compound grown by either the HP method 15) or the MC method 16) as source materials; the thin films were subsequently annealed in an H 2 S atmosphere. All thin films annealed above 400 °C in H 2 S atmosphere successfully formed CuInS 2 in the crystal phase.…”
Section: Introductionmentioning
confidence: 99%